L’enseignant dans la pensée de Castoriadis : évaluation et clôture symbolique dans l’éducation - Loïc Clavier (Éducation et Socialisation)
Rational control, as a social imaginary of capitalist society impact she and school " educations to." In this neoliberal society that places the rationalization of the human as the basis of the objectives of the company regulations throne assessment that sorts, directs, Coast and is adorned with the objectivity of rationality. Can subsume the lock that is the practice of evaluation on the fence in the direction of the school. It is necessary to examine this paradox between the situation of the teacher in Castoriadis must remove the student from the possession of knowledge and evaluative practice in examination classes. It is, in our context, to clarify how the teacher can both be the one under " educations to " aims to promote strategies instituent ( unlock the closure of established meaning ) among students in a sense of autonomy and who, through evaluative practice (Clavier , 2001) , maintains the set.